STAT3-Specific Single Domain Nanobody Inhibits Expansion of Pathogenic Th17 Responses and Suppresses Uveitis in Mice - Mbanefo, Evaristus C.; Yan, Ming; Kang, Minkyung; Alhakeem, Sahar A.; Jittayasothorn, Yingyos; Yu, Cheng-Rong; Parihar, Ashutosh; Singh, Sunanda; Egwuagu, Charles E. (Frontiers in Immunology, 2021)
STAT3 activates transcription of genes that regulate cell growth, differentiation and survival and genetic deletion of Stat3 in T cells abrogates Th17 differentiation, suggesting that STAT3 is a potential therapeutic target for Th17-mediated diseases. However, a major impediment to therapeutic targeting of intracellular proteins such as STAT3 is the lack of efficient methods for delivering STAT3 inhibitors into cells. In this study, we developed a novel antibody (SBT-100) comprised of the variable (V) region of a STAT3-specific heavy chain molecule and demonstrated that this 15 kDa STAT3-specific nanobody (SBT-100) enters human and mouse cells, induced suppression of STAT3 activation and lymphocyte proliferation in concentration dependent manner. To investigate whether SBT-100 would be effective in suppressing inflammation in vivo, we induced experimental autoimmune uveitis in C57BL/6J mice by active immunization with the ocular autoantigen, interphotoreceptor retinoid binding protein (IRBP). Analysis of the retina by fundoscopy, histological examination or optical coherence tomography showed that treatment of the mice with SBT-100 suppressed uveitis by inhibiting expansion of pathogenic Th17 cells that mediate EAU. Electroretinographic (ERG) recordings of dark and light adapted a- and b-waves showed that SBT-100 treatment rescued the mice from developing significant visual impairment that characterize EAU in untreated mice. Adoptive transfer of activated IRBP-specific T cells from untreated EAU mice induced EAU, while EAU was significantly attenuated in mice that received IRBP-specific T cells from SBT-100 treated mice. Taken together, these results demonstrate efficacy of SBT-100 in mice and suggests its therapeutic potential for human autoimmune diseases.